Program Fisioterapi Pada Pasien Post ORIF Fracture Tibial Plateau Sinistra Dengan Pemasangan Plate and Screw: Case Report - Aulia Intamiara Devi; Wijianto Wijianto (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Fractures are one of the causes of disability due to trauma due to accidents. The internal fixation used in this case is in the form of plates and screws in the form of iron plates and screws that are attached to the broken bones so that they function as immobilization. Tibial fractures are serious but rare injuries accounting for approximately 1.2% of all fractures. Tibial fractures are noted to occur in young men and elderly women with osteoporosis representing up to 8% of all fractures. With 72% in patients older than 55 years. The condition of Post ORIF Fracture Tibial Plateau causes pain, edema, decreased joint range of motion, muscle weakness, and decreased ability to functional activities. The implementation of the physiotherapy program in this case aims to determine the effect of providing physiotherapy interventions in the form of Transcutaneous Electrical Nerve Stimulation (TENS), Ankle Pumping Exercise, Static Exercise, Hold Relax, and Active Resisted Exercise in reducing pain, reducing edema, increasing joint range of motion, increasing strength. muscles, and optimizing the functional activity of Post ORIF Fracture Tibial Plateau. This research method was carried out directly to 1 respondent with the condition of Post ORIF Fracture Tibial Plateau Sinistra by giving therapy as much as 4 therapy sessions. After four sessions of therapy, the results were decreased pain, decreased edema, increased range of motion, increased muscle strength, and increased functional activity. The conclusion was that the physiotherapy program in the case of Post ORIF Fracture Tibial Plateau Sinistra was proven to be able to reduce pain, edema, increase joint range of motion, increase muscle strength, and increase functional activity.Keywords: Fracture, Post ORIF Fracture Tibial Plateau, Transcutaneous Electrical Nerve Stimulation, Exercise Therapy